Small savings policy: circumventing tax sops - Moorthy, Vivek (2003)
Inflation benchmarking of small savings and provident fund interest rates, which is a sound policy in and of itself, has the added advantage of lowering the interest paid when there is inflation and tax exemptions cannot be touched. - Reproduced.
Keywords: Taxation; Savings